La complexité de valeurs dans la politique étrangère de l'administration Reagan face à l'Iran - Lecours, André (Études internationales, 1996)
The formulation of a policy that will satisfy several values and interests more or less compatible is a classic problem of political decision making. This phenomenon by which there can be, in a foreign policy issue for example, several divergent values and interests was named value-complexity by Alexander George. When facing a value complexity problem, a decision maker must choose some values and some interests over others. The choice he makes will not necessarily be the one made by other decision makers. This can result in a serious impediment to the decision making process. The American foreign policy towards the Middle East faced, for the major part of the Cold War era, a value-complexity problem because it looked to reconcile four hard-to reconcile values and interests. The Reagan government was confronted rather acutely with this problem in the making of its Iranian policies. The administration was split in at least two factions over Iran : one who thought primarily of containing the Soviet Union in the Middle East region and the other for whom the political stability of moderate regimes threatened by revolutionnary Iran should be the most important priority. The existence of these factions, consequence of value-complexity, produced the making and the implementation of two distinct Iranian policies.